Implementation of Telepharmacy Services in Community Pharmacy – Pharmacists’ Perspective in Republic of Serbia - Ilkić, Jovana; Obradović, D.; Milošević Georgiev, Andrijana; Marinković, Valentina; Tadić, Ivana (Indian Journal of Pharmaceutical Education and Research, 2023)
Aim/Background: COVID-19 pandemic has casted a new light over the capacity of telepharmacy to increase access to pharmaceutical care, providing more support to patients and allowing new opportunities for pharmacists. However, telepharmacy still hasn’t been introduced as a standardised pharmaceutical service in the Republic of Serbia, therefore, the objective of this paper is to assess the potential for its local implementation by exploring the perspectives of community pharmacists. Materials and Methods: Semi-structured one-on-one interviews were conducted online from January to March 2021, with pharmacists working in community pharmacies across the country (n=23). The questions were developed to ensure the consistency and comprehensibility of the interviews, while keeping the questions flexible enough to allow each participant to share their understanding of telepharmacy, its application, benefits and risks, but also their motivating factors, ideas, and views on overall capacity to introduce such services. Interviews were transcribed ad verbatim, coded and thematically analysed. Results: The participants had a good theoretical understanding and were mostly open and ready for the introduction of new services, but due to the lack of regulatory, financial and organisational solutions, participants believed that this is still not possible, especially since remote healthcare services still aren’t recognised by the national law of Serbia. Conclusion: Although many pharmacists were willing to support patients remotely and have done so on their own in the past, there is a need for further initiatives in order to introduce structured and standardised telepharmacy services in the Republic of Serbia.
Keywords: Telehealth; Telemedicine; Pharmaceutical care; Pharmacy services; Public health